2008
DOI: 10.1261/rna.972008
|View full text |Cite
|
Sign up to set email alerts
|

miR-148 targets human DNMT3b protein coding region

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules of 20-24 nucleotides that regulate gene expression. In animals, miRNAs form imperfect interactions with sequences in the 39 Untranslated region (39UTR) of mRNAs, causing translational inhibition and mRNA decay. In contrast, plant miRNAs mostly associate with protein coding regions. Here we show that human miR-148 represses DNA methyltransferase 3b (Dnmt3b) gene expression through a region in its coding sequence. This region is evolutionary conserved and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
350
3
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(380 citation statements)
references
References 33 publications
(44 reference statements)
19
350
3
8
Order By: Relevance
“…This suggests that miR-148a may not directly target RUNX3. Previous studies have already confirmed that miR-148a could modulate DNMT1 and DNMT3B protein expression (Braconi et al, 2010;Duursma et al, 2008;Pan et al, 2010;Zhu et al, 2012). Therefore, our results show that overexpression of miR148a in gastric cancer cells might upregulate RUNX3 expression through the modulation of DNMTs.…”
Section: Overexpression Of Mir-148a Downregulated Runx3 Gene Expressionsupporting
confidence: 79%
“…This suggests that miR-148a may not directly target RUNX3. Previous studies have already confirmed that miR-148a could modulate DNMT1 and DNMT3B protein expression (Braconi et al, 2010;Duursma et al, 2008;Pan et al, 2010;Zhu et al, 2012). Therefore, our results show that overexpression of miR148a in gastric cancer cells might upregulate RUNX3 expression through the modulation of DNMTs.…”
Section: Overexpression Of Mir-148a Downregulated Runx3 Gene Expressionsupporting
confidence: 79%
“…This is in consistence with the most recent work demonstrating that miRNAs can interact with the coding region of mRNA 45,46 . For example, miR-148 represses DNA methyltransferase 3b gene expression through a region in its coding sequence 47 . Strikingly, we found that the binding sites of miR-484 in the amino acid coding sequences of Fis1 are evolutionarily conserved in many species, including human, rat and mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Target sites of animal and human mRNAs are usually at the 3'-untranslated region (UTR), although there are examples of target sites in the coding region as well (Duursma et al, 2008).…”
Section: Biogenesis Of Mirnas and Gene Regulation By Mirnasmentioning
confidence: 99%